Analysis of environmental health risks from exposure to polyethylene terephthalate microplastics in refilled drinking water - S. Kasim; A. Daud; A.B. Birawida; A. Mallongi; A.I. Arundana; A. Rasul; M. Hatta (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Microplastic pollution has a far and wide presence in the surroundings. It can be encountered in the sea, wastewater, freshwater, food, air, and water sources. It is even present in refilled drinking water. This study aims to analyze environmental health dangers of the exposure to polyethylene terephthalate microplastics in refilled water sources in Tamangapa, Makassar City, Indonesia.METHODS: This research is an observational study with an environmental health risk analysis. Sampling was conducted in Tamangapa, Makassar City, Indonesia. A total of 100 respondents were involved. Additionally, 20 samples of refilled drinking water were examined in the laboratory using the Fourier Transform Infrared test. Data analysis was carried out by calculating the intake and risk quotient values. If risk quotient > 1, it is considered necessary to carry out risk management.FINDINGS: An average polyethylene terephthalate microplastic concentration of 0.0052 milligram per kilogram per day, an average intake rate of 210 milligrams per kilogram per day, an average exposure frequency of 350 days, an average exposure duration of 30 years, average intake exposure to polyethylene terephthalate microplastics above 0.0004, and an average risk quotient value above 1 were obtained. If they build up in the body, microplastics may have harmful consequences, including organ inflammation, internal or external damage, and chemical alteration of plastics that have already entered the body.CONCLUSION: Some measures of risk management that can be performed are to reduce the concentration of risk agents if the pattern and timing of consumption cannot be changed, reduce the consumption pattern (intake rate) if the concentration of risk agents and the time of consumption cannot be changed, and reduce the contact time if the risk agent concentration and consumption pattern cannot be changed.